IMPLEMENTATION OF THE STUNTING REDUCTION ACCELERATION POLICY THROUGH SPECIFIC NUTRITION INTERVENTIONS: A STUDY OF MOTHERS AND CHILDREN IN SEWULAN VILLAGE, DAGANGAN DISTRICT, MADIUN REGENCY: IMPLEMENTASI KEBIJAKAN PERCEPATAN PENURUNAN STUNTING MELALUI INTERVENSI GIZI SPESIFIK ANAK DI DESA SEWULAN KECAMATAN DAGANGAN KABUPATEN MADIUN - Muryani; Harianto; Endang Murti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Stunting remains a major public health issue in Indonesia due to its long-term impacts on children's physical growth, cognitive development, and future productivity. To address this problem, the Indonesian government has implemented the Accelerated Stunting Reduction Policy through specific nutrition interventions targeting mothers and children during the first 1,000 days of life. This study aims to analyze the implementation of the accelerated stunting reduction policy through specific nutrition interventions in Sewulan Village, Dagangan District, Madiun Regency. The research employs a qualitative descriptive approach within the framework of public policy implementation. Data were collected through interviews, observations, and documentation involving village government officials, health workers, integrated health service post (Posyandu) cadres, and beneficiary families. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the policy has generally been carried out according to established guidelines through activities such as maternal and child health services, growth monitoring, nutrition education, supplementary feeding programs, immunization, and regular Posyandu services. Supporting factors include the commitment of local stakeholders, active participation of health cadres, and collaboration among relevant institutions. However, several challenges remain, including limited public awareness regarding nutritional fulfillment, inconsistent participation of beneficiaries, and resource constraints in program implementation. These obstacles affect the effectiveness of specific nutrition interventions in reducing stunting prevalence. The study concludes that the implementation of the accelerated stunting reduction policy in Sewulan Village has contributed positively to improving maternal and child health outcomes. Nevertheless, strengthening community education, stakeholder coordination, and program monitoring is necessary to enhance the effectiveness and sustainability of stunting reduction efforts.